Beverage clouding agents: Review of principles and current manufacturing. Issue 7 (3rd October 2018) - Stounbjerg, Lykke; Vestergaard, Christian; Andreasen, Birgitte; Ipsen, Richard
ABSTRACT: Clouding agents are additives applied in fruit-flavored beverages to achieve a visual appearance similar to fresh juice. They consist of dispersions of small particles that impart turbidity. Use of emulsions is the most well established methodology utilized by the beverage industry, but citrus pulp, pigments, and biopolymer microgels are also employed in the manufacturing of clouding agents. Long product shelf life is a prime requirement and hence instability is a perpetual concern. Often, clouding agents are produced concentrated, and thus they must be stable both as concentrates and in the final beverage. The composition and manufacturing processes can be adapted to modify the physicochemical characteristics of the clouding agent, and systems that are metastable, but still have sufficient stability can be achieved. In this review article, the impact of, amongst other parameters, oil, weighting agent, emulsifier, stabilizer, as well as pressure, heat, pH and shear on turbidity and physical product stability will be discussed.